Radiographic findings after stereotactic body radiation therapy for stage I non-small cell lung carcinomas: retrospective analysis of 90 patients. Issue 4 (22nd December 2020) - Menoux, I.; Antoni, D.; Santelmo, N.; Truntzer, P.; Schumacher, C.; Labani, A.; Noël, G.
Abstract: Aim: Stereotactic body radiation therapy for lung tumours can expose patients to radiation pneumonitis (RP) (<6 months after irradiation) and lung fibrosis (beyond 6 months). The aim of this study was to describe post-irradiation radiographics appearances. Materials and methods: This retrospective study of 90 patients with a stage I non-small cell lung carcinoma reports a detailed description of the computed tomography (CT) or positron emission tomography/CT changes that can be observed after treatment, according to modified Kimura score for RP and Koenig's classification for fibrosis. This evaluation was realised at 1 month and then every 3–4 months, with a median follow-up of 35 months. Results: The most common radiological RP pattern was diffuse consolidation. It appears in a mean time of 4 months and reaches its maximum at 9 months after radiotherapy. Seventy-three per cent of the RP evolved to fibrosis. Most of these findings were encompassed in the 35 Gy isodose. Findings: Radiological parenchymal changes are frequent in the treatment region, which renders the tumour response monitoring by tumour size, particularly by response evaluation criteria in solid tumours, unsuitable.